Teaching methods to improve the speaking skill on 9th grade students of. Camilo Gallegos Domínguez High School, Arenillas. Period 2016-2017 - Ajila Apolo, Sonia Elizabeth; Toro Villamar, Alicia Estefanía (Machala : Universidad Técnica de Machala, 2016)
El trabajo de investigación actual ha tenido como finalidad analizar y señalar cuáles de los métodos de enseñanza son los más adecuados para ayudar a los docentes en la mejora de la capacidad de hablar en los alumnos, lo que debe centrarse en el medio ambiente y las necesidades de la Estudiantes. En el campo de la enseñanza de una lengua extranjera como el inglés, existen varios métodos destinados a mejorar las habilidades orales que nos permiten promover una práctica activa; Dentro de varios, los más deseables son, el método directo, el audio, el método lingual, la Respuesta Física Total, el Enfoque Comunicativo, entre otros. El proyecto de investigación también contribuye a asumir características en relación con el tipo y diseño de la investigación descriptiva en la escuela secundaria porque describe los hechos, causas y manifestaciones del fenómeno o problema tal y como se observó en su contexto natural.
The current investigative work has had as purpose to analyze and state which from all the teaching methods are the most adequate in order to help teachers in the improvement of the ability of speaking in students, which should be focused on the environment and the needs of the learners. In the field of teaching a foreign language like English, there are several methods aimed to improve oral skills which allow us to promote an active practice; within several ones, the most desirable are, the direct method, audio, lingual method, the Total Physical Response, the Communicative Approach, among others. The investigative project also contributes to assume characteristics in relation to the type and design of descriptive investigation in high school because it describes the facts, causes, and manifestations of the phenomenon or problem as it was observed in its natural context.
Keywords: STUDENT; SPEAKING; FOREIGN; LANGUAGE